1974
DOI: 10.1128/iai.10.6.1370-1377.1974
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Progesterone on Neisseria gonorrhoeae

Abstract: The effects of progesterone on the growth of pathogenic and nonpathogenic species of Neisseria were studied in liquid cultures. Only strains of N. gonorrhoeae and N. meningitidis were highly sensitive to growth inhibition by progesterone. This inhibitory effect was either bacteriostatic or bactericidal, depending upon the ratio of progesterone concentration to cell mass. The site of progesterone inhibition appeared to be located in the cell membrane; >86% of [4-4C]progesterone was recovered in the lipid-contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

1977
1977
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 26 publications
2
22
0
Order By: Relevance
“…Exogenous estradiol administered to ovariectomized rats produced a prolonged increase in vaginal bacterial levels from 5X104 to 1X108 organisms/sample. Other investigations have demonstrated that steroid hormones inhibit the growth of pure cultures of a variety of Gram-positive bacteria (Yotis 1967), as well as Neisseria gonorrhoeae (Morse & Fitzgerald 1974).…”
Section: Discussionmentioning
confidence: 99%
“…Exogenous estradiol administered to ovariectomized rats produced a prolonged increase in vaginal bacterial levels from 5X104 to 1X108 organisms/sample. Other investigations have demonstrated that steroid hormones inhibit the growth of pure cultures of a variety of Gram-positive bacteria (Yotis 1967), as well as Neisseria gonorrhoeae (Morse & Fitzgerald 1974).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings generally support the concept that variation in the recoverability of gonococci from cervices of women at different points in their menstrual cycles is due to the action of progesterone or progesterone-like substances. Progesterone has previously been shown to have a bacteriostatic effect on gonococci in vitro (7,17,20). This is probably responsible for the relatively reduced recovery of organisms from women who are not menstruating.…”
Section: Discussionmentioning
confidence: 99%
“…Some aspects of steroid uptake may reflect binding to the cell wall rather than actual utilization. Morse and Fitzgerald (23) observed that binding of [14C]progesterone was three times greater to Neisseria species which were metabolically sensitive to the steroid than to insensitive cells. In our study, the uptake of steroids appeared to reflect an active metabolic process, since the uptake was temperature dependent and resulted in the detection of an unknown labeled by-product with an Rf value intermediate between those of progesterone and estradiol.…”
Section: Methodsmentioning
confidence: 99%